Challenges Relating to the Collection and Distribution of Royalties for Musical Works in Cameroon - Obi , Ngole (International Journal of Law and Policy, 2023)
Purpose: The purpose of the study was to explore and analyze the challenges related to the collection and distribution of royalties for musical works in Cameroon. The music industry plays a significant role in the cultural and economic development of the country, making it crucial to ensure a fair and efficient system for royalty management.[1] Methodology: The study employed qualitative method that involved a combination of literature review, interviews, and analysis of existing data. Relevant literature on royalty collection and distribution systems in both national and international settings were examined to provide a comprehensive understanding of the subject matter.[2] Findings: The findings of this study highlighted several significant challenges faced in the collection and distribution of royalties. These issues contribute to the overall inefficiency and unfairness of the current royalty system, resulting in financial loss of artists. Based on the research findings, several recommendations are proposed to address the identified challenges. Unique Contribution to Theory, Practice and Policy: The theory of the research sheds light on the specific challenges faced by rights holders in musical arts in Cameroon, providing a comprehensive understanding of the complex dynamics of the local music industry.[3] In terms of policy, this study has the potential to influence the development and implementation of policies related to royalty collection and distribution in Cameroon. The research findings and recommendations can be used as evidence-based insights by policymakers, copyright organizations, and government agencies to shape new policies or reform existing ones.[4] Overall, the unique contribution of this study lies in its comprehensive analysis of the challenges faced in the collection and distribution of royalties for musical works as well as its practical recommendations for addressing these challenges. By bridging the gap between theory, practice, and policy, this research aims to make a meaningful impact on the music industry in Cameroon and potentially serve as a reference for similar contexts globally.